1999
DOI: 10.1111/j.1749-6632.1999.tb07895.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Gene Families in the Nematode Caenorhabditis elegansa

Abstract: Neuropeptides have diverse roles in the function and development of the nervous system. With the completion of the sequencing of the C. elegans genome, rapid identification of nematode neuropeptide genes is possible. To date, 41 C. elegans neuropeptide genes have been identified. Of these genes, 20 genes, named flp (FMRFamide-like peptide) genes, encode FMRFamide-related proteins (FaRPs). Deletion of one of the flp genes, flp-1, results in several behavioral defects, suggesting that at least one flp gene is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(55 citation statements)
references
References 68 publications
1
54
0
Order By: Relevance
“…With the PHB-specific neuropeptide-like promoter fusion nlp-1::gfp (Li et al, 1999), we found that hlh-14 mutants lacked PHB neurons. With the PHA-specific promoter fusions flp-15::gfp (Li et al, 1999) and osm-10::gfp ) (PHA-specific in adults), we found no alteration in the number of PHA neurons in hlh-14 mutants.…”
Section: Hlh-14 Mutants Are Missing Hsn Motoneurons and Phb Sensory Nmentioning
confidence: 99%
See 3 more Smart Citations
“…With the PHB-specific neuropeptide-like promoter fusion nlp-1::gfp (Li et al, 1999), we found that hlh-14 mutants lacked PHB neurons. With the PHA-specific promoter fusions flp-15::gfp (Li et al, 1999) and osm-10::gfp ) (PHA-specific in adults), we found no alteration in the number of PHA neurons in hlh-14 mutants.…”
Section: Hlh-14 Mutants Are Missing Hsn Motoneurons and Phb Sensory Nmentioning
confidence: 99%
“…LG III gmIs12 [srb-6::gfp] (N. Hawkins, personal communication) (Troemel et al, 1995), gmIs21[nlp-1::gfp] (Li et al, 1999).…”
Section: Elegans Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…FMRFamide-related peptides may act excitatory or inhibitory on their target cells (depending on the target cell type) and they are involved in reproduction, feeding, and many other behaviors (3,5,(14)(15)(16)(17)(18). The abundance, complexity, and importance of FMRFamide peptides within an invertebrate species, is illustrated by the fact that the nematode worm Caenorhabditis elegans contains at least 20 FMRFamide preprohormone genes, and that the deletion of only one of these genes causes severe behavioral defects (5,17,19).…”
mentioning
confidence: 99%